2008
DOI: 10.1002/micr.20538
|View full text |Cite
|
Sign up to set email alerts
|

Customized reconstruction with the free anterolateral thigh perforator flap

Abstract: From April of 2003 through September of 2006, 70 free anterolateral thigh (ALT) flaps were transferred for reconstructing soft-tissue defects. The overall success rate was 96%. Among 70 free ALT flaps, 11 were elevated as cutaneous ALT septocutaneous vessel flaps. Fifty-seven were harvested as cutaneous ALT myocutaneous "true" perforator flaps. Two flaps were used as fasciocutaneous perforator flaps based on independent skin vessels. Fifty-four ALT flaps were used for lower extremity reconstruction, 11 flaps w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 42 publications
0
20
0
3
Order By: Relevance
“…These defects were then classified into groups A to C with the respective flap harvesting for the tongue reconstructions. 2,11,[13][14][15][16]30,31 In group C, an anterolateral thigh myocutaneous flap was designed in a pentagonal shape to recreate the missing tongue (Figs. 16 and 17).…”
Section: Surgical Techniquementioning
confidence: 99%
“…These defects were then classified into groups A to C with the respective flap harvesting for the tongue reconstructions. 2,11,[13][14][15][16]30,31 In group C, an anterolateral thigh myocutaneous flap was designed in a pentagonal shape to recreate the missing tongue (Figs. 16 and 17).…”
Section: Surgical Techniquementioning
confidence: 99%
“…Its versatility in which thickness and volume can be adjusted, leads to a perfect match of customized reconstruction. 9 We used an islanded anterolateral thigh flap with some bulk of vastus lateralis to cover a deep defect in the groin following lymph node dissection and radiotherapy. It has been shown that with anterolateral thigh flap varying sizes of vastus lateralis can be harvested.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the anterolateral thigh free flap has increased dramatically in recent years due to its recognized reliability, potential size, relative ease of harvesting, and minimal donor morbidity 55,56. Harvesting the flap with the patient in the supine position is an attractive feature of this flap that must not be underappreciated, particularly in the multiply injured war-wounded patient.…”
Section: Free Tissue Transfermentioning
confidence: 99%